Myosteatosis as an independent risk factor for mortality after kidney allograft transplantation: a retrospective cohort study. Issue 1 (5th November 2021) - Morel, Antoine; Ouamri, Yaniss; Canouï‐Poitrine, Florence; Mulé, Sébastien; Champy, Cécile Maud; Ingels, Alexandre; Audard, Vincent; Luciani, Alain; Grimbert, Philippe; Matignon, Marie; Pigneur, Frédéric; Stehlé, Thomas
Abstract: Background: Patients with end‐stage renal disease may display both a loss of skeletal muscle mass and an increase in muscle fat deposits. We aimed to analyse the impact of low skeletal muscle mass index (SMI, surrogate marker of sarcopenia) and low muscle density (MD, surrogate marker of myosteatosis) on patient survival after kidney transplantation (KT). Methods: In a retrospective cohort of 200 kidney transplant recipients (KTr), we measured on an unenhanced cross‐sectional computed tomography scan taken at the level of the third lumbar vertebra within the previous year or at the time of KT, both SMI (muscle cross‐sectional area normalized for height 2, reported in cm 2 /m 2 ) and MD (mean attenuation of muscle cross‐sectional area, expressed in Hounsfield units). We determined age‐specific and sex‐specific normality thresholds on 130 healthy subjects. The baseline factors associated with low MD were assessed by logistic regression analysis. Cox proportional hazard univariable and multivariable models were constructed to identify predictive factors of patient survival. Results: Among the 200 patients of the cohort, 123 were male (62%), and mean age was 54.8 ± 13.8 years. A total of 181 KTr required renal replacement therapy before KT (91%), and 36 KTr (18%) received repeat kidney transplant after previous failed KT. Mean MD was 30.6 ± 9 HU in men and 29.7 ± 8.3 HU in women, whereas SMI was 49.7 ± 8.6 cm 2 /m 2 in men and 42.3 ± 7.3 cm 2 /m 2 in women. MD was below the 2.5th percentile for the healthy population in 49 KTr (25%), defining the myosteatosis group, while SMI was below the 2.5th percentile for the reference population in 10 KTr (5%). Independent risk factors for myosteatosis were two or more KT [adjusted odds ratio (aOR) 5.2, 95% confidence interval (95% CI): 2.22–12.4, P  = 0.0001], a history of stroke (aOR 3.7, 95% CI: 1.30–10.7, P  = 0.015), and body mass index > 25 kg/m 2 (aOR 2.94, 95% CI: 1.4–6.18, P  = 0.004). Myosteatosis was independently associated with mortality [adjusted hazard ratio (aHR) 2.12, 95% CI: 1.06–4.24, P  = 0.033], as were cardiovascular disease (HR 2.06, 95% CI: 1.02–4.15, P  = 0.043) and age (aHR 1.06, 95% CI: 1.03–1.09, P  = 0.0003). Low SMI was not associated with mortality. Conclusions: Myosteatosis, which was more prevalent than low skeletal muscle mass, might be an important prognostic marker in patients undergoing KT.